School performance in pubertal adolescents with dysmenorrhea - Syamsir Alam; Hakimi Hakimi; Tiangsa Sembiring; Melda Deliana; Siska Mayasari Lubis (Paediatrica Indonesiana, 2011)
Background Dysmenorrhea is a common gynecological symptom reported in adolescent girls. Prevalence of the condition has been reported to be 45 - 75%. Absenteeism from work and school as a result of dysmenorrhea is common (13 - 51% of women have been absent at least once, and 5 - 14% are often absent due to the severity of symptoms).Objective To compare school performance in pubertal adolescent girls with and without dysmenorrhea.Methods This cross-sectional study was conducted in June 2010 in adolescent females aged 12 - 18 years from the Musthafawiyah School, Mandailing Natal district, North Sumatera. Adolescent females with and without dysmenorrhea were recruited for this study. All participants completed questionnaires including age of menarche, length of menstrual cycle, length of bleeding, number of sanitary napkins used daily and school absences. School reports from two consecutive semesters in one year were used to evaluate subjects’ academic performance. An academic score of higher than 7.5 was considered good performance while scores of less than 7.5 were considered poor. We used the chi-square test to analyze differences in school performance between girls with and without dysmenorrhea.Results One hundred and sixteen participants were divided into 2 groups, those with and without dysmenorrhea, of 58 subjects each. We found no significant difference in school performance between the two groups, P=0.176 (95% CI -0.009 to -0.048 and P=0.08 (95%CI -0.052 to 0.024).Conclusion There was no significant difference in school performance of girls with and without dysmenorrhea.